(untitled) - Pitts, Robert A. (Mason, OH, 2006)
Strategic management: Building and sustaining competitive advantage shows you in detail how the world's top companies build, extend, and sustain a competitive advantage. How do they do it? Through distinctive competence, quality, globalization, change, and ethics. And because this business textbook is rich with study tools, Strategic management: Building and sustaining competitive advantage gives you the competitive advantage on the test as well!
Keywords: Strategic planning,Industrial management,Competition; Case studies,Case studies,Case studies; United States,United States,United States